GO BAR – a conceptual business model for enhancing the well-being of the poor community - Syed Jahir, Afnan Munir; Ahmad Dahlan, Abdul Rahman; Hassan, Ahmad Hasrul Yusdi (IEEE Explore, 2018)
The purpose of this paper is a conceptual solution to help people who hoping to donate in the easier ways and to help the receiver of the donate gain through mobile application platform. ”GO BAR” is a business modal which provides application that can make donation transfer using online transaction. This application also help the society gain more donation faster through the technology as nowadays the world are approaching the technology world. Literature reviews, benchmarking, Business Modal Canvas (BMC), 4 lenses of Innovation, and Value Proposition Canvas(VPC) has been used as the methodologies for this paper.